Part 2: Review and establish threshold levels in foods of the priority allergens - Baumert, Joseph (2021)
The main purpose of this second meeting was to establish threshold levels in foods of the priority allergens. Based on the defined approach, the Expert Committee discussed and agreed on the safety objective, which could be described as “to minimise, to a point where further refinement does not meaningfully reduce health impact, the probability of any clinically relevant objective allergic response, as defined by dose distribution modelling of minimum eliciting doses (MEDs) and supported by data regarding severity of symptoms in the likely range of envisioned Reference Doses (RfD)”. The Committee further identified several important considerations to guide decision-making. These included a clear definition of criteria to be met by quantitative data on which reference doses (RfD) are based, supporting data on health manifestations (severity) at the proposed RfD, quality, quantity, availability and accessibility of data (for priority allergens), as well as how to deal with priority allergens for which information supporting one or more of those considerations was lacking.